2014
DOI: 10.1002/14651858.cd002281.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Powered versus manual toothbrushing for oral health

Abstract: Analysis 8.3. Comparison 8 Unknown or other action versus manual toothbrushes, Outcome 3 Gingival scores >3 months at all sites..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
286
1
25

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(323 citation statements)
references
References 102 publications
11
286
1
25
Order By: Relevance
“…4 weeks or longer) by the Cochrane Collaboration first published in 2003 and subsequently updated comparing manual and power toothbrush effectiveness (13)(14)(15). Beginning in 2003, the Cochrane Collaboration Oral Health group published a systematic review examining more than 30 years of published studies and oscillating-rotating toothbrushes consistently demonstrated a statistically significant benefit over manual toothbrushes (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 weeks or longer) by the Cochrane Collaboration first published in 2003 and subsequently updated comparing manual and power toothbrush effectiveness (13)(14)(15). Beginning in 2003, the Cochrane Collaboration Oral Health group published a systematic review examining more than 30 years of published studies and oscillating-rotating toothbrushes consistently demonstrated a statistically significant benefit over manual toothbrushes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions from this independent research group were 'brushes with a rotationoscillation action removed plaque and reduced gingivitis more effectively than manual brushes in the short-term and reduced gingivitis scores in studies over 3 months'. Once again, a new systematic review was conducted and published in 2014 by the Cochrane Oral Health group reviewing evidence (56 studies) to assess the effects of using a power toothbrush compared with using a manual toothbrush for maintaining oral health and similar findings were obtained (15). Thirteen trials, involving 979 total participants, utilized the Quigley-Hein (Turesky) index to assess plaque removal of oscillating-rotating and manual toothbrushes in the 2014 review.…”
Section: Discussionmentioning
confidence: 99%
“…6 Contemporary power toothbrushes are proving to be even more efficient in removing plaque, specifically brushes with an oscillating rotating head, which have been consistently shown in a Cochrane systematic review 7 and two subsequent updates 8,9 to be more effective than manual brushes in removing plaque and reducing gingivitis in both the short-and long-term. …”
Section: Toothbrushing Evolutionmentioning
confidence: 97%
“…Haydar 4 quoted by Mackenzie is about efficacy of a toothbrush with a special design, whilst the systematic reviews [5][6][7] quoted concern powered brushing. Whilst we know that different toothbrush designs -including powered brushes -may have an effect on plaque control, the focus of our study was on standard manual brushes which the vast majority of the global population use.…”
Section: Bilateral Guidelinesmentioning
confidence: 99%